GENE-19. TARGETED SEQUENCING PANEL (TODAI ONCOPANEL) FOR VARIOUS TYPES OF BRAIN TUMORS. (11th November 2019) - Takayanagi, Shunsaku; Tanaka, Shota; Miyawaki, Satoru; Shin, Masahiro; Nakatomi, Hirofumi; Shinozaki-Ushiku, Aya; Oseto, Kumiko; Kohsaka, Shinji; Oda, Katutoshi; Aburatani, Hiroyuki; Mano, Hiroyuki; Saito, Nobuhito
Abstract: BACKGROUND: Todai OncoPanel (TOP) is a targeted sequencing panel newly invented by the University of Tokyo, which allows us to prospectively investigate on genomic abnormalities of multiple cancer-related genes. The objective of this study was to assess its role in molecular diagnosis as well as in patient treatment. METHODS: Thirteen cases of brain tumors were analyzed: 10 gliomas and glioneural tumors, 2 meningiomas, and 1 intracranial sarcoma. DNA and RNA were obtained from tumor samples; DNA was obtained from peripheral blood as well. The TOP DNA panel analyzed point mutations, insertions, deletions, and copy number variations of 464 cancer-related genes. The TOP RNA panel detected fusions, exon skipping, and expression abnormalities of 463 genes. RESULTS: In all cases of gliomas, the tumor content was abundantly high and the analysis was performed with sufficient depth. The IDH1/2 mutation status and chromosome 1p/19q status were completely consistent with those obtained by Sanger sequencing and microsatellite analysis. In benign brain tumors, the tumor content tended to be low. The number of gene mutations identified also tended to be low. In a case of glioneuronal tumor, FGFR2 mutation was recognized, but there was no clinical trials of FGFR inhibitors open in Japan yet. DISCUSSION: TOP is useful as an aid for molecular diagnosis of gliomas. In spite of some targetable genetic abnormalities detected in the tested tumors, its efficacy may be limited by the scant availability of respective molecularly targeted agents.